A responsabilidade social empresarial e o direito - Ferreira, Cassia Bianca Lebrão Cavalari (2006)
The social liability of the companies although is based in ethics, on this paper it will be seen under a legal view. To accomplish it the study of the constitutional principles, of the social liability, and solidarity is necessary. The terminology of liability was also treated, suggesting the substitution of it to solidarity. The focus was to find the identity of the social liability of the companies in the legal system, due to the fact that the qualification of the institutes is fundamental to its comprehension. From this point, the possibility of regulation of the social liability has been analyzed. The benefits obtained by the social liability behavior and its abuse were also pointed